Survey on cyber deception - Zhao-peng JIA; Bin-xing FANG; Chao-ge LIU; Qi-xu LIU; Jian-bao LIN (Tongxin xuebao)
The asymmetric situation of network attacks and defenses is one of the key issues of current network security.Cyber deception was a revolutionary technology introduced by defenders to alter the asymmetric situation.By thwarting an attacker's cognitive processes，defenders can mislead attackers，hence causing them to take specific actions that aid network security defenses.In this way，defenders can log attackers'behavior and method，increase cost for the attackers to launch a successful attack，as well as reduce the probability of an attacker's success.Cyber deception formally and classify cyber deception into four classes was defined.Then，the cyber deceptions’development was divided into three stages，and each stage’s character was decided.Next，a hierarchical model to describe the existing work was proposed.At last，the countermeasures in cyber deception and the development trends in this field was discussed.